2002
DOI: 10.1016/s0014-5793(02)03108-3
|View full text |Cite
|
Sign up to set email alerts
|

Resistin expression and regulation in mouse pituitary

Abstract: Resistin, a new adipocytokine, is expressed in human, rat and mouse adipose tissue. Its putative role as a mediator of insulin resistance is controversial. We hypothesized that resistin, in common with leptin, has multiple roles in non-adipose tissues. Using reverse transcription polymerase chain reaction (RT-PCR) we show that the resistin gene (Retn) is expressed in mouse brain (hypothalamus and cortex) and pituitary gland. Immunohistochemistry revealed resistin protein in the arcuate nucleus and pituitary gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
0
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(102 citation statements)
references
References 28 publications
11
84
0
7
Order By: Relevance
“…ERK1/2-MAPK phosphorylation was only affected in rat GCs. Protein and mRNA expression of resistin have been described in several tissues of the reproductive axis (Morash et al 2002, Nogueiras et al 2004, Brown et al 2005, Tovar et al 2005. Furthermore, resistin mRNA is expressed in the bovine mammary gland, and its expression in this tissue decreases during lactation (Komatsu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ERK1/2-MAPK phosphorylation was only affected in rat GCs. Protein and mRNA expression of resistin have been described in several tissues of the reproductive axis (Morash et al 2002, Nogueiras et al 2004, Brown et al 2005, Tovar et al 2005. Furthermore, resistin mRNA is expressed in the bovine mammary gland, and its expression in this tissue decreases during lactation (Komatsu et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, expression of resistin (mRNA and protein) has been reported in several reproductive tissues including hypothalamus (Morash et al 2002, Tovar et al 2005, pituitary (Morash et al 2002, Brown et al 2005, and testis (Nogueiras et al 2004). In hypothalamus, resistin has been shown to inhibit feeding (Tovar et al 2005, Vazquez et al 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, resistin is almost exclusively expressed in white adipose tissue in proportion to adipocyte differentiation and the amount of adipose tissue [3]. It has also been found in the pituitary gland, the hypothalamus, and in the blood circulation [20]. Resistin in rats is secreted not only by adipose tissue, but has also been found in the gastrointestinal tract, adrenal glands, skeletal muscles, pancreas, and spleen [21,22,23].…”
Section: Sites Of Resistin Productionmentioning
confidence: 99%
“…58 Resistin is a 12.5 kDa cysteine-rich, C-terminal protein, whose mRNA expression has been predominantly observed in white adipose tissue, and to a lesser extent in the hypothalamus, the pituitary, BAT, the stomach, the large intestine, the adrenal gland and skeletal muscles, in rats. [59][60][61] In vitro studies showed that resistin is induced during adipocyte differentiation 53,57,62 and, as suggested by its signal sequence, is secreted into the media. 53 Mouse studies also showed that resistin is detectable in the serum, demonstrating that it can circulate in the blood.…”
Section: Resistinmentioning
confidence: 99%